Narrativas sobre inclusão de crianças com necessidades educacionais especiais em uma escola municipal de educação básica de Cuiabá - MT - Carvalho, Sandra Pavoeiro Tavares (2017)
This research has as theme children with special educational needs (SEN), and is inserted in discussions about School Inclusion, considering the dimensions that permeate the teacher's performance: public policies, school organization and teacher training. Based on a qualitative approach and the presuppositions of narrative research, this study was developed in a Basic Education Municipal School in Cuiabá-MT, comprising nine participants, two members of the management team, five teachers working in the classroom and two in a multifuncitonal resource room. The aim of the study was to understand what teachers and managers say about their performance with children with SEN in the 1st Cycle of Elementary Education, how they are signifying and reaffirming their professional practice and what experiences they have had with these children. The information obtained through the analysis of documents, observations, conversations and field notes gave rise to narrative texts that allowed the characterization of the school unit, its administrative and pedagogical organization form. According to the management team, the educational unit guides its actions through the principles of democratic management, guarantees the access and permanence of children from six to nine years of age at school and mobilizes teachers so that school inclusion and literacy goals are achieved. Through oral narratives, classroom teachers shared their experiences with students diagnosed with autism and physical and intellectual disabilities, stating that, when faced with the news that they had to work with these children, they experienced reactions and feelings of fear, anxiety and insecurity. Although they have a degree in Pedagogy and are considered experienced in teaching, they find difficulties in the learning process of children with SEN and do not feel prepared for them, because due, to their complexity, these conditions require the rethinking of the organization of the school, classroom, curricula and established forms of social interaction. The performance of these teachers occurs through a clinical perspective, based on deficient aspects presented by the children. The teachers who work with the students in the multifunctional resource rooms, when narrating the developed work, stated that the specialized educational service is also supported in a clinical perspective and, although it is defined as complementary to the service carried out in a common classroom, no interlocution between teachers is observed. The experiences and stories told by the research participants indicate that School Inclusion of children with SEN is a challenge to be faced and much is still required in this aspect. Although the education of these children is ensured by a vast legal apparatus, school actions are distant from what documents propose. Many weaknesses at the school and by the teachers occur, as well as the contradictions present in the education system that legally aim in attending to diversity and, at the same time, with its demands, ignores the differences between students, teachers and the School context.